Cooperativism 2.0: internet presence and e-commerce development in the olive catalan cooperatives - Cristóbal Fransi, Eduard; Montegut Salla, Yolanda; Daries Ramon, Natalia (REVESCO. Revista de Estudios Cooperativos, 2017)
Nowadays the role of ICT in business management is a subject of growing interest to both academics and professionals. Web 2.0 has emerged as an important source of innovation that contributes to organizational performance and improving the firm’s competitiveness in the agricultural sector. However, evidence has been found that reveal the difficulties for the entry of these technologies in agribusinesses and their application for effective e-commerce. According to the above, this research seeks to know whether the Web sites of the olive cooperatives facilitate effective communication with their target audiences and are tailored to electronic commerce. In order to do this, it is proposed first of all, a model for the analysis of Web pages oil cooperatives, based on the content analysis technique, considering the dimensions of Information, Communication, e-Commerce and Additional Functions. Secondly the eMICA methodology (Extended Model of Internet Commerce Adoption) applies, to identify opportunities arising from the use of Web 2.0 tools and improve the deficiencies detected for a more competitive management. From the results we can draw that much it remains margin for improvement in the adoption of electronic commerce by Catalan cooperatives in the olive sector. The fact that only 5.8% of websites have reached the stage 3 in the eMica model indicates the low level of functional maturity reached by cooperatives in the development of their Web sites. The results of analysis of web content corroborate these statements.